2009
DOI: 10.1590/s1413-35552009005000048
|View full text |Cite
|
Sign up to set email alerts
|

Perfil do pesquisador fisioterapeuta brasileiro

Abstract: Objective: To define the profile of the Brazilian physical therapy researcher in terms of training, productive outcomes, and grants and fellowships awarded by Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), an agency linked to the Ministry of Science and Technology and dedicated to promoting scientific research and developing human resources for research in Brazil. Methods:We assessed the online curricula vitae of every Ph.D. physical therapy researcher available in the Lattes database (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
20

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 6 publications
1
23
0
20
Order By: Relevance
“…We found a relatively low rate of activity of masters and PhDs in the universities, which can be explained by the rapid growth in the number of PhD physical therapists in Brazil, around 900% between 1998 and 2008 8 . In this same period, the number of undergraduate courses grew by 435% 27 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We found a relatively low rate of activity of masters and PhDs in the universities, which can be explained by the rapid growth in the number of PhD physical therapists in Brazil, around 900% between 1998 and 2008 8 . In this same period, the number of undergraduate courses grew by 435% 27 .…”
Section: Discussionmentioning
confidence: 79%
“…In this same period, the number of undergraduate courses grew by 435% 27 . According to the study by Coury (2009), it is possible to observe that public universities have more PhDs than private ones, in a relation of 5.6 PhDs per public universities to 0.84 for private ones. Therefore, there is still work for PhDs, including in private universities 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These extension programs are extremely important in academic life, because they allow for the development of educational and assistance initiatives that benefit the population that practices physical activities. It also encompasses teaching and research, which enriches academic experiences even more, in addition to being an exercise of mutual contribution in which students, professors, PSIs, and communities are involved 18 . Only 20% of the PSIs offer graduate programs in the area of Sports Physical Therapy, which can be directly related to the large quantity of specialist professionals graduated in similar areas other than Sports Physical Therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that only 1% of the sample was composed of professionals with doctorate. Coury and Vilella 16 pointed out an increase of 90% in the number of doctors with a degree in physiotherapy in the last decade 16 . This fact is added with the findings of this study: among professionals who continued their studies, 85% chose a lato sensu course.…”
Section: A I L Y L I V I N G a C T I V I T Y A C T I V I T Y A N D mentioning
confidence: 99%